Evaluation of a Walking-Track Intervention to Increase Children's Physical Activity during Primary School Break Times - Emma Powell; Lorayne A. Woodfield; Alexander J. Powell; Alan M. Nevill; Tony D. Myers (MDPI AG, 2018)
Despite the known benefits of engaging in daily moderate to vigorous physical activity (MVPA), only 22% of children in England are meeting the recommended guidelines. School break times have been advocated as a key part of children’s daily routines in which their MVPA can be increased. The main aim of this study was to evaluate the effect of installing a walking-track on children’s MVPA during school break times. A mixed method design was employed which allowed for the quantitative measurement of children’s PA at three time points (baseline, mid-intervention (1–5 weeks) and follow-up (6–9 weeks)), using pedometers (n = 81, 5–9 years) and systematic observation (n = 23, 7–9 years). A semi-structured interview (n = 1) was also conducted at 10 weeks’ follow-up. The installation of the walking-track was grounded in a unique set of theoretical constructs to aid the behaviour change of the teachers. Short term positive increases in girls’ and boys’ MVPA and longer term increases in boys’ vigorous PA (VPA) were found. Qualitative data highlighted that boys dominated the walking-track and the inconsistent behaviour of school staff negatively impacted upon children’s MVPA. A set of principles to guide the installment of walking-tracks in school playgrounds are recommended.